Protective immunity enhanced Salmonella vaccine vectors delivering Helicobacter pylori antigens reduce H. pylori stomach colonization in mice - Ghasemi, Amir; Wang, Shifeng; Sahay, Bikash; Abbott, Jeffrey R.; Curtiss, Roy (Frontiers in Immunology, 2022)
Helicobacter pylori is a leading cause of gastric mucosal inflammation, peptic ulcers, and gastric adenocarcinoma. Emerging antimicrobial-resistant H. pylori has hampered the successful eradication of frequent chronic infections. Additionally, due to the absence of effective vaccines against H. pylori, a safe vaccine is highly demanded. In this study, we employed a new innovative Protective Immunity Enhanced Salmonella Vaccine (PIESV) vector strain to deliver and express multiple H. pylori antigen genes. Immunization of mice with our vaccine delivering the HpaA, Hp-NAP, UreA and UreB antigens, provided sterile protection against H. pylori SS1 infection in 7 out of 10 tested mice. Compared to the control groups that had received PBS or a PIESV with an empty vector, immunized mice exhibited specific and significant cellular recall responses and antigen-specific IgG2c, IgG1, total IgG and gastric IgA antibody titers. In conclusion, an improved S. Typhimurium-based live vaccine delivering four antigens shows promise as a safe and effective vaccine against H. pylori infection.